Pembentukan Karakter Dalam Pembelajaran IPS Di era Revolusi Industri 5.0 Di MI Ma’arif NU Metenggeng Purbalingga - Sundari, Dewi (Fakultas Tarbiah Institut Agama Islam (IAI) Hamzanwadi Pancor Lombok Timur, 2025)
In the era of Industrial Revolution 5.0, both challenges and opportunities have emerged in primary education due to the integration of smart technologies and human-centered values. This study explores the development of students' character through Social Studies (IPS) learning at MI Ma’arif NU Metenggeng, Purbalingga. Employing a qualitative-descriptive approach, data were collected through participatory observation, semi-structured interviews with teachers and students, and analysis of lesson plan documents. Using an interactive analysis model comprising data reduction, presentation, and verification, the study identified best practices such as the integration of locally relevant project-based learning, reflective discussions, and the use of digital media—such as interactive social maps and online collaboration platforms—to instill values of discipline, empathy, social responsibility, and honesty. The findings indicate that this approach not only enhances intellectual abilities but also strengthens students' character as a foundation for navigating the complexities of the modern era. The study recommends ongoing professional development for teachers in designing innovative Social Studies activities and involving parents in providing feedback on students' character development. This learning model is expected to serve as a reference for other madrasahs and primary schools in fostering character education in the 5.0 era. Keywords: Industrial Revolution 5.0; Social Studies Learning; Character Education; Madrasah Ibtidaiyah; Technology Integration.